2009
DOI: 10.1017/s0376892909990038
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal cycles and long-term trends in abundance and species composition of sharks associated with cage diving ecotourism activities in Hawaii

Abstract: SUMMARYShark cage diving is both popular and controversial, with proponents citing educational value and non-extractive use of natural resources and opponents raising concerns about public safety and ecological impacts. Logbook data collected 2004–2008 from two Oahu (Hawaii) shark cage diving operations were analysed to determine whether such voluntary records provide useful insights into shark ecology or ecotourism impacts. Operators correctly identified common shark species and documented gross seasonal cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 20 publications
6
74
2
Order By: Relevance
“…BRUVs have become the standard tool for monitoring large-bodied, potentially cautious reef fish including sharks (Meekan & Cappo 2004, Malcolm et al 2007). BRUVs are non-invasive, repeatable, and allow the collection of data on the relative abundance and distribution of the marine faunal community (Harvey et al 1996(Harvey et al , 2001, particularly for motile fauna.…”
Section: Baited Remote Underwater Video Systems (Bruvs)mentioning
confidence: 99%
See 3 more Smart Citations
“…BRUVs have become the standard tool for monitoring large-bodied, potentially cautious reef fish including sharks (Meekan & Cappo 2004, Malcolm et al 2007). BRUVs are non-invasive, repeatable, and allow the collection of data on the relative abundance and distribution of the marine faunal community (Harvey et al 1996(Harvey et al , 2001, particularly for motile fauna.…”
Section: Baited Remote Underwater Video Systems (Bruvs)mentioning
confidence: 99%
“…BRUV surveys were conducted simultaneously (within 30 min of each other) in a paired design so that one system was at a dived site and one was in an adjacent, undived site. To precise ly assess the distance travelled by a bait plume, Cappo et al (2004) developed an equation that considers current speeds and tidal movements; however, currents on Palmyra's forereefs are highly variable and unpredictable and we were unable to use this equation to inform our study design. Previous studies have demonstrated that distances of 100 m (Ellis & Demartini 1995) and 450 m (Cappo et al 2004) be tween simultaneously deployed BRUV systems were adequate to ensure independence.…”
Section: Baited Remote Underwater Video Systems (Bruvs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The most common technique for allowing tourists to see Great White sharks (Carcharodon carcharias) and pelagic sharks such as the Silky (Carcharhinus falsiformis), Galapagos (C. galapagensis), Sandbar (C. plumbeus) and Tiger sharks (Galeorcerdo cuvier), either from boats or through scuba (and cage) diving, is known as 'chumming' [4,5,6]; it is also known in Australia as 'berleying' [7,8]. Chumming or berleying involves placing blood and/or liquidized tiny fish parts in the water to create an oily slick that sharks can sense and follow to the boat (or the divers) [5].…”
Section: Issn: 2348-9804mentioning
confidence: 99%